Relevance of the Principle of Precaution in the Preparation of the Deed of Statement of Decisions of the Extraordinary General Meeting of Shareholders (Egms) of Pt Nissihinkan Indonesia (Case Study ) Decision Court Tall Banten Number: 74/Pdt/2021/Pt. Btn ) - Noviantika Melati Sukma; Widodo Tresno Novianto; Hari Purwadi (MultiTech Publisher, 2025)
A notary is a public official authorized by the Ministry of Law and Human Rights. One of their responsibilities includes creating a Statement of Meeting Resolutions (PKR) based on the Extraordinary General Meeting of Shareholders (EGMS). This research examines the importance of a notary's adherence to the principle of prudence when drafting a PKR Deed based on fabricated meeting minutes, using Decision Number 74/PDT/2021/PT.BTN as a case study. The research employs a normative legal approach with a case study focus. The findings indicate that Lusi Indriani, SH, M.Kn, as a notary, violated procedural rules by failing to apply the principle of prudence. Consequently, the PKR deed number 01 she issued was deemed legally defective and annulled, along with its associated documents, resulting in Lusi receiving a written warning as a penalty.